Rhythmic Self-Entrainment. A Panacea - Leclair, Jacqueline (Revue musicale OICRM, 2025)
This article proposes rhythmic self-entrainment (RSE)—commonly referred to as “subdividing”—as a possible solution for the types of malaise many post-secondary music students experience during daily music practice: frustration, mindlessness, excessive stress, and anxiety. While RSE is traditionally taught to help students improve musically, this article shows how it could also be implemented as an effective method for improving mental health. Considering the context of rising mental health crises that affect post-secondary students worldwide, improvements in music student mental health are urgently needed. Necessarily speculative in nature, this article examines RSE through the lenses of various musical, psychological, and philosophical disciplines, and explains how RSE offers the potential to profoundly improve music student mental health.